2008
DOI: 10.1089/ten.a.2007.0060
|View full text |Cite
|
Sign up to set email alerts
|

Regulable Vascular Endothelial Growth Factor165 Overexpression by Ex Vivo Expanded Keratinocyte Cultures Promotes Matrix Formation, Angiogenesis, and Healing in Porcine Full-Thickness Wounds

Abstract: The intricate wound repair process involves the interplay of numerous cells and proteins. Using a porcine full-thickness wound (FTW) healing model, we hypothesized that the ex vivo gene transfer of vascular endothelial growth factor (VEGF)-transfected basal keratinocyte (KC) cell suspensions may generate cross-talk and induce matrix formation, angiogenesis, and accelerated healing. Moreover, to regulate overexpression of isoform 165 of VEGF and its effect on healing, we introduced a tetracycline (TC)-inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Apart from EPC, other (stem) cell sources have been considered to vascularize wounds and efforts have mostly been made in the field of mesenchymal stem cells (MSC) [22,23]. In addition to cell therapy, angiogenic growth factor therapy [e.g., vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), plateletderived growth factor (PDGF), and placental growth factor (PlGF)] has been explored to grow vessels in nonhealing or chronic wounds [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from EPC, other (stem) cell sources have been considered to vascularize wounds and efforts have mostly been made in the field of mesenchymal stem cells (MSC) [22,23]. In addition to cell therapy, angiogenic growth factor therapy [e.g., vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), plateletderived growth factor (PDGF), and placental growth factor (PlGF)] has been explored to grow vessels in nonhealing or chronic wounds [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF165 is a role to play in the main form which has the strongest activity and is most widely distributed [2]. Gene therapy with VEGF has been shown to promote therapeutic angiogenesis in preclinical models of tissue ischemia and in human clinical trials [3,4,5,6]. The present results indicate that VEGF165 is a promising candidate for gene therapy in wound healing applications.…”
Section: Discussionmentioning
confidence: 53%
“…Subsequently in 1990, they demonstrated in vivo hGH expression after transplantation of the transfected keratinocytes in nude mice, as first ex vivo gene delivery to wounds [19]. The potential application of this approach to promote wound healing has been explored by various researchers [2024]. In particular, we have demonstrated that ex vivo delivery of hEGF can significantly improve the healing of porcine full-thickness wounds [4, 7].…”
Section: Discussionmentioning
confidence: 99%